Dampak Adopsi TI Terhadap Kinerja Perusahaan Multinasional - Muhammad Ihsan Fawzi; Apol Pribadi Subriadi (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2022)
This study aims to classify and provide an overview of the factors that influence the adoption of IT in multinational companies and the impact of IT adoption on the performance of multinational companies. The data for this study were obtained from literature searches published from 2009 to 2021. The searches were conducted on scientific journals published internationally in Elsevier or Science Direct, Emerald Insight, Willey, Taylor and Francis, and the Academy of Taiwan Information Systems Research. The search results related to themes and variables, obtained about 150 articles and selected 40 articles relevant to IT adoption in multinational companies and the impact of IT adoption on the performance of multinational companies. The results showed that technological factors, organizational factors, and environmental factors influenced IT adoption, although technological factors and organizational factors influenced IT adoption more than environmental factors. In addition, IT adoption has a positive impact on the performance of multinational companies, especially economic performance and operational performance. Even so, several studies say that IT adoption does not have a positive impact on the performance of multinational companies. The results of this study also show that to find out the factors that influence IT adoption in multinational companies is to use the TOE framework. IT adoption also has a positive impact on the performance of multinational companies, especially in terms of economic performance and operational performance.